2022
DOI: 10.1088/1755-1315/1109/1/012103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mangrove and seagrass ecosystem on marine productivity of Pramuka Island, Seribu Islands, Indonesia

Abstract: The connectivity between seagrass and mangrove ecosystems has synergistic benefits of conserving the land-sea ecosystems of the small islands. The physicochemical properties of the two ecosystems lead to the success of the habitat of the interconnected zone. This study aimed to analyze the physicochemical factors in the mangrove and seagrass ecosystems on Pramuka Island and understand the factors influencing the phytoplankton production of small island coastal ecosystems. Sediment and water collection were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Mangroves can also prevent sedimentation by binding dissolved sediment from rivers and suppressing the rate of seawater intrusion toward the mainland [6]. In addition, mangrove ecosystem has the function as a carbon sink and storage [7] [43]. The potential of carbon storage can be analyzed in the stand structure of mangroves and sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves can also prevent sedimentation by binding dissolved sediment from rivers and suppressing the rate of seawater intrusion toward the mainland [6]. In addition, mangrove ecosystem has the function as a carbon sink and storage [7] [43]. The potential of carbon storage can be analyzed in the stand structure of mangroves and sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate chemistry and pH Mangrove, seagrass, coral (Akhand et al, 2021;Camp et al, 2016;George & Lugendo, 2022;Macklin et al, 2019;Middelburg et al, 1996;Saderne et al, 2019) Mangrove, seagrass (Salma et al, 2022;Sandoval-Gil et al, 2016) Mangrove, coral (Camp et al, 2019;Yates et al, 2014a) Seagrass, coral (Unsworth et al, 2012) Mangrove (Chen et al, 2021;Sippo et al, 2016) Seagrass (Barry et al, 2013;Bergstrom et al, 2019;Cyronak et al, 2018;Koweek et al, 2018;Ow et al, 2016;Ricart et al, 2021)…”
Section: Referencesmentioning
confidence: 99%
“…Furthermore, a study of six different locations along the Australian coast by Sippo et al (2016) demonstrated that mangroves exported DIC and alkalinity to adjacent waters (Figure 2.4) thus creating a buffer against ocean acidification Water pH and alkalinity exhibit high variability within seasons, days, and even hours due to tidal variation, temperature, light intensity, and local hydrodynamic conditions, as well as biotic factors (Cyronak et al, 2018;Saderne et al, 2019). Salma et al (2022) found no significant differences in water pH between mangrovedominated sites, seagrass-dominated sites, and sites where mangroves and seagrass co-occur. Consequently, the results regarding the relative contribution of crossecosystem connectivity to ocean acidification buffering are often contradictory and highly dependent on local conditions.…”
Section: Ph and Carbonate Unbalancementioning
confidence: 99%